Strategi Komunikasi Akun Aniesbubble di Twitter dalam Meningkatkan Engagement - Safira Triandharini; Teddy Kurnia Wirakusumah; Detta Rahmawan (Institut Nalanda, 2024)
In view of the increased impact of social media, non-profit organization (NPOs) should review their communication strategies in social media to manage their relation with followers. This papers aims to examine which non profit organizational type of content that enhance high public engagement in Twitter. Using a quantitative content analysis of aniesbubble, tweets during campaign election period with 78 tweets are being classified into three different message function; information-community-action. One-way ANOVA was applied to test the effects of these message function and public engagement on Twitter which is likes and retweet. Findings revealed a significant effects among non profit message function and engagement in Twitter. The findings shows that community message function achieve the highest engagement among the others.